The association between animal source foods and stunting in children aged 6 months to 5 years: A systematic review - Shapiro, Myra Joy; Downs, Shauna; Quelhas, Diana; Kreis, Katharine; Kraemer, Klaus; Fanzo, Jessica (2017)
Children under the age of 5 are at a critical stage of growth and development requiring the support of adequate nutrition. Stunting is a measure of failure to reach linear growth potential and can be used as an indicator of reductions in neurodevelopment and cognitive function, elevated risk of morbidity and mortality in childhood and chronic disease in adulthood. The aim of this study was to examine the relationship between the consumption of animal source foods (ASF) and stunting in low- and middle-income countries. A systematic review was conducted using the CINAHL, Embase, Global Index Medicus, PubMed, and Web of Science databases. To identify gray literature, the sources examined were the International Food Policy Research Institute publications, the New York Academy of Medicine Grey Literature Report, OpenGrey, and Proquest Digital Dissertations. Studies that quantified ASF consumption by frequency, quantity, or both in children 6 to 59 months in low- and middle-income countries were included in the review. The primary outcome was linear growth and the secondary outcomes were micronutrient deficiencies. Study titles, abstracts, and full texts obtained in the searches were independently screened by two reviewers. The title review contained 13,431 references; 205 were eligible for abstract review. Of the 89 full texts eligible for review, the majority were excluded for ASF consumption that was not adequately quantified for analysis (n=26). Other exclusion reasons included growth and/or micronutrient deficiency outcomes absent or the relationship between outcomes and ASF consumption not established (n=24), children <6 months or >59 months (n=11), data from a high-income country (n=3), excluded language (n=1) and review articles (n=1). A total of 19 studies (23 articles) were included in the final review. The majority of studies were observational (n=13); the designs were longitudinal (n=8) and cross-sectional (n=5). The majority of observational studies (n=9) used a 24-hour recall to collect ASF consumption, but the consumption variables varied widely from binary measures of dietary ASF to counts of daily ASF consumed to grams of ASF protein intake. Intervention studies (n=6) examined the use of a variety of foods from caterpillar cereal to meat and fish powders. This review found a diverse range of studies examining ASF and stunting in young children, however, the heterogeneity of ASF consumption measures is a challenge for direct comparisons of results.